Effect of Chelating Agents on Push-Out Bond Strength of NeoMTA Plus to Root Canal Dentin - Pattath Kunjan Anju; Tina P. Purayil; Kishore Ginjupalli; Nidambur V. Ballal (Association of Support to Oral Health Research (APESB), 2022)
Objective: To evaluate and compare the effect of 17% Ethylenediaminetetraacetic Acid (EDTA), 9% Etidronic acid (HEDP), and 7% Maleic acid (MA) on the push-out bond strength of NeoMTA Plus sealer to the coronal, middle, and apical thirds of root canal dentin. Material and Methods: Forty single-rooted human maxillary central incisors were selected and decoronated to 12 mm long root fragments. Working length was established and root canals were then enlarged up to rotary Protaper F3. After each instrumentation, the root canal was irrigated with 2.5% NaOCl. For the final irrigation regimen, the specimens were divided into 4 groups (n=10) and treated with EDTA, HEDP, MA or Saline. Root canals were coated with NeoMTA Plus sealer, and obturation was done with single cone obturation technique. Subsequently, three horizontal sections were taken from the coronal, middle and apical thirds of each specimen, and POBS was measured using a universal testing machine. The type of bond failures was assessed under a stereomicroscope. Statistical analysis was done with One-way ANOVA with Tukey's Post hoc analysis. Results: MA and EDTA showed the highest POBS. There was no significant difference in bond strength between MA and EDTA (p>0.05). HEDP and Saline showed lower POBS. Among all the four groups, the coronal third showed the highest values, followed by middle and apical thirds. Conclusion: The type of chelating agent used during the root canal treatment significantly affects the bond strength of NeoMTA Plus to the root canal dentin.